Energy harvesting for low-power autonomous devices and systems - Rastegar, Jahangir; Dhadwal, Harbans Singh (SPIE tutorial texts ;, 2016)
"This book is an introductory text describing methods of harvesting electrical energy from mechanical potential and kinetic energy. The book focuses on the methods of transferring mechanical energy to energy conversion transducers of various types, including piezoelectric, electromagnetic, electrostatic, and magnetostrictive transducers. Methods that have been developed for collecting, conditioning, and delivering the generated electrical energy to a load, as well as their potential use as self-powered sensors are described. The book should be of interest to those who want to know the potentials as well as shortcomings of energy harvesting technology. The book is particularly useful for energy harvesting system designers as it provides a systematic approach to the selection of the proper transduction mechanisms and methods of interfacing with a host system and electrical energy collection and conditioning options. An extensive bibliography is provided to direct the reader to appropriate references for detailed material not included in the book"--